The European Central Bank's operational framework and what it is missing - Giulia Gotti; Francesco Papadia (Bruegel, 2024)
This paper attempts to fill in the gaps in the European Central Bank's framework review. In March 2024, the European Central Bank published the results of a review of its operational framework. After discussing how the ECB operational framework has changed since the Great Financial Crisis, we provide an assessment of the review, which we deem as premature, and highlight some gaps it has not resolved. First, the choice of a hybrid system is attractive, but needs a precise specification. Second, the review did not specify the timing of the introduction of structural long-term refinancing operations and a structural portfolio of securities. We find that these measures should be implemented when the level of excess liquidity reaches between exteuro1.3 trillion and exteuro2 trillion, projected between mid-2026 and late 2027. Finally, as the introduction of a digital euro could impact bank liquidity, it is crucial to design a framework that can flexibly increase the supply of central bank liquidity.
Keywords: F14; F21; F23; F60; 330; European Central Bank; EU governance; monetary policy; fiscal policy